Masterpieces, investment and representation : goldsmithery of the central Slovak mining towns in the early modern period - Hodásová, Barbara (2022)
The title of the book may appear confused in content at first sight. The selected goldsmiths’ works always represent the starting point for wider considerations in the field of the art history of the specific micro-region. Although the four chapters are understood more as case studies and still cannot be regarded as synthesizing works, their titles already ask questions, which apply more comprehensively to the interpretation of early modern art in the central Slovak mining towns. Thus, specific goldsmiths’ works originated in various circumstances, and the texts of the case studies published here are an attempt to identify the different alternatives. Domestic works on one side and imports on the other are not vertically placed in hierarchical positions, but rather contextualized in the specific frameworks in which they originated or circulated after their completion. They represented inter-cultural contacts or active artistic communication of a specific micro-region in both inward and outward directions